Analisis Tingkat Kepatuhan Partai Politik Dari Hasil Audit Pelaporan Keuangan Dana Kampanye Peserta Pemilu - Muhammad Aqiil Fahreza Yofiansyah; Rida Perwita Sari (CV. KAMPUSA AKADEMIK PUBLISING, 2024)
This research explores the level of compliance of political parties in campaign fund auditing, with a focus on Party X in City A. A descriptive qualitative approach is used to analyze various aspects of compliance, including regulatory understanding, transaction recording, and campaign fund reporting. The research findings show that Party X's liaison officers still do not fully understand the guidelines of General Election Commission Regulation (PKPU) Number 18 of 2023 and General Election Commission (KPU) Decree Number 1677 related to campaign finance reporting. This resulted in the recording of transactions that were not detailed and inaccurate reporting. This study recommends increasing political party officials' understanding of regulations, improving recording and reporting systems, and strengthening election accounting to improve compliance and transparency in the use of campaign funds.